Категорії аксіологічного підходу в сучасному правовому дискурсі - Фальковський, Андрій Олександрович; Фальковский, Андрей Александрович; Fal'kovs'kij, A. (My University, 2012)
In the article the author tries to show of the speciﬁ city of Axiological Approach’s categories in a modern legal Discourse. The base categories аt the Axiological Approach are: value, estimation, valuable orientations and values of Law. The author comes to conclusion about expediency of the using of these categories in modern jurisprudence and legal practice.
Фальковський А. О. Категорії аксіологічного підходу в сучасному правовому дискурсі / А. О. Фальковський // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 52-59.
Keywords: аксіологічний підхід; категоріїї аксіологічного підходу; категории аксиологического подхода; аксиологический подход; axiological approach; Category axiological approach